Assessment of Emulsification Potentials and Bio- Diversities of Bacterial Isolates from Bonny Loading Jetty Crude Oil Polluted Soil, Bonny Island, Rivers State. - Ezenwelu, Chijioke O.; Arazu, Amarachukwu V.; Chukwudozie, Izuchukwu; Emeka, Oparaji H. (European Journal of Applied Sciences, 2022)
Surfactant producing microorganisms are indispensable in utility; In the present study, contaminated homogenized soil samples from Bonny Island River showed the following physicochemical properties: pH (5.67), Chloride ion (Cl-) (321±0.2 mg/g),Potassium ion (K+) (5.26±0.01mg/g), Magnesium ion(Mg2+) (2.19±0.05 mg/g), Iron II ion(Fe2+) (38.73±0.13ppm), Calcium ion (Ca2+) (4.12±0.1mg/g), Copper II ion (Cu2+) (3.2±0.01ppm), Lead II ion (Pb2+) (0.21±0.02 ppm), Phosphate ion (PO3) (6.24±0.1 mg/g), Total petroleum hydrocarbons(TPH 364±0.05 Mg/g), Total organic carbon (TOC 56.5±0.05 mg/g) and Total organic matter contents (TOM) (63.45±0.2) .Prior to the emulsification screening carried out; microbial isolation and total heterotrophic counting (CFU/g) carried out showed a total of twelve microbial distinct isolates from the polluted soil with a microbial population of 2.5 x 108 and 2.1 x 108 CFU/g of the soil. Dilution folds of 10-1 and 10-2 from the Bushnell-Hass media showed microbial population of 0.33 x 104 and 0.78 x 104CFU/g respectively. Klebsiella sp. showed emulsification indices of43.3%, 51.2%, 50 and 48.9%with diesel and coconut oil, kerosene and crude oil respectively. Pseudomonas sp. showed emulsification indices of 40, 43, 54 and 45.6% with diesel, coconut oil, kerosene and crude oil respectively. Bacillus sp. showed emulsification indices of 46, 45, 32 and 37% with diesel, coconut oil, kerosene and crude oil respectively. The present study have shown the great potential of utilization of the bacterial consortium in oil recovering from various damp oil-wells and in cost efficient bioremediation process.